2012
DOI: 10.1016/j.neuroimage.2011.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Short separation channel location impacts the performance of short channel regression in NIRS

Abstract: Near-Infrared Spectroscopy (NIRS) allows the recovery of cortical oxy-and deoxyhemoglobin changes associated with evoked brain activity. NIRS is a back-reflection measurement making it very sensitive to the superficial layers of the head, i.e. the skin and the skull, where systemic interference occurs. As a result, the NIRS signal is strongly contaminated with systemic interference of superficial origin. A recent approach to overcome this problem has been the use of additional short source-detector separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
287
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(297 citation statements)
references
References 46 publications
8
287
1
1
Order By: Relevance
“…Gagnon et al 35 investigated cortical versus superficial oxygenation changes elucidated from a finger tapping task during simultaneous fNIRS and BOLD fMRI. In addition, yet another group looked at cortical activation during apple peeling using fNIRS and fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Gagnon et al 35 investigated cortical versus superficial oxygenation changes elucidated from a finger tapping task during simultaneous fNIRS and BOLD fMRI. In addition, yet another group looked at cortical activation during apple peeling using fNIRS and fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…In Saager et al (2011) an improved version of the approach was presented using an 8-channel probe configuration and 2 small SD channels (5 mm). Gagnon et al (2011Gagnon et al ( , 2012 investigated how the position of the short SD channel relative to the long SD channel impacts the performance of the method. They concluded that the separation between the channel of interest and the regressor distance should be b 1.5 cm.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…These systemic phenomena typically occur in the superficial tissues (mainly the scalp) and can confound the readings of the instruments, especially when task related physiological responses happen [6,7]. A multi-channel configuration with sensors placed at different distances from the injection point is the solution that is currently being adopted in CW fNIRS to reduce the crosstalk between the superficial systemic signal and the deep cortical signal [8][9][10]. Conversely, in the time domain (TD) approach to fNIRS, picosecond pulsed lasers and fast photodetectors are used to acquire the photon distribution of time-of-flights in the head.…”
Section: Introductionmentioning
confidence: 99%